Intercompreensão de línguas românicas: repercussões no campo educacional potiguar - Silva, Ana Catarina de Melo (2017)
Intercomprehension is a centuries-old communicative practice. This natural process was scientifically turned into a system during the 1990’s, and thenceforth presented amongst the plural approaches and inserted into the Didactics of plurilingualism. In the educational domain, plurilingual projects help to diversify teaching, as they allow for the integration of the multiple areas of knowledge and promote mutual respect amongst languages/cultures. Under this perspective, how are actions directed at intercomprehension being carried out within the Brazilian context and, more specifically, within that of the Brazilian state of Rio Grande do Norte? This research aims generally at identifying actions already carried out in favor of intercomprehension on national and local levels, in order to focus on the imminent repercussions for the state educational scenario. This research, which has an exploratory and descriptive goal (GERHARDT and SILVEIRA, 2009), and which is also structured following the new perspectives from Applied Linguistics (RAJAGOPALAN, 2003 and MOITA LOPES, 2013, 2016), uses as tools the questionnaire and the semi-directive interview (QUIVY and CAMPENHOUDT, 1998). The analytical procedures are based on content analysis (BARDIN, 1979), as well as on the theoretical references presented, the scope of which integrates intercomprehension, education and teacher education: Beacco et al, 2015; Caddéo and Jamet, 2013; Capucho, 2013; De Carlo, 2010; Escudé, 2011; Martins, 2014; Meissner, 2008; Muñoz and Burgos, 2013; Freire, 2011; Saviani, 2009; Gadotti, 2012; Nóvoa, 2009, 2012; Palma Filho, 2010, amongst others. The subjects of the research come from three groups: professors from Brazilian universities (I); participants in the I Colóquio de Intercompreensão de Natal (1st Intercomprehension Colloquy in Natal) and UFRN students enrolled in the Intercomprehension for Romance Languages course (II), and Elementary Education professionals working at municipal public schools (III). Results point to an expansion of actions favoring intercomprehension in the academia as well as in schools, most of all through partnership between universities and secretariats of education. Amongst ongoing or already concluded researches one can observe a significant amount of delimitations focused on the classroom. From these results one can conclude that this research contributes not only to promote intercomprehension but also to pave the way to new investigations on the theme. After all, data points to the possibility of a multiplication in the number of intercomprehenders in the state of Rio Grande do Norte as we consider the first marked repercussions in the context of that state education.